2011
DOI: 10.1016/s0140-6736(11)60698-3
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of early intensive multifactorial therapy on 5-year cardiovascular outcomes in individuals with type 2 diabetes detected by screening (ADDITION-Europe): a cluster-randomised trial

Abstract: SummaryBackgroundIntensive treatment of multiple cardiovascular risk factors can halve mortality among people with established type 2 diabetes. We investigated the effect of early multifactorial treatment after diagnosis by screening.MethodsIn a pragmatic, cluster-randomised, parallel-group trial done in Denmark, the Netherlands, and the UK, 343 general practices were randomly assigned screening of registered patients aged 40–69 years without known diabetes followed by routine care of diabetes or screening fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
468
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 408 publications
(491 citation statements)
references
References 33 publications
15
468
0
4
Order By: Relevance
“…Both populations were predominantly white. It is of interest to compare the SOUL-D participants with the wellcharacterised patient cohort of the UKPDS, which recruited people with newly diagnosed type 2 diabetes from primary care across the UK between 1977 and 1991 [2,22] and the recent European Anglo-Danish-Dutch study of Intensive Treatment In PeOple with screeN detected diabetes in primary care (ADDITION-Europe) study, which recruited people diagnosed according to local diabetes screening policies in three European countries into an intervention targeting cardiovascular risk [6]. Looking first at the historical perspective, the SOUL-D cohort has a higher mean BMI than UKPDS (32.3 vs 27.5 kg/m 2 ), presumably a reflection of the known increase in obesity over the 20 years since the UKPDS sample was recruited [23], but smoking was less prevalent (19.8% vs 35% in UKPDS), perhaps reflecting the success of recent public health interventions [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both populations were predominantly white. It is of interest to compare the SOUL-D participants with the wellcharacterised patient cohort of the UKPDS, which recruited people with newly diagnosed type 2 diabetes from primary care across the UK between 1977 and 1991 [2,22] and the recent European Anglo-Danish-Dutch study of Intensive Treatment In PeOple with screeN detected diabetes in primary care (ADDITION-Europe) study, which recruited people diagnosed according to local diabetes screening policies in three European countries into an intervention targeting cardiovascular risk [6]. Looking first at the historical perspective, the SOUL-D cohort has a higher mean BMI than UKPDS (32.3 vs 27.5 kg/m 2 ), presumably a reflection of the known increase in obesity over the 20 years since the UKPDS sample was recruited [23], but smoking was less prevalent (19.8% vs 35% in UKPDS), perhaps reflecting the success of recent public health interventions [24].…”
Section: Discussionmentioning
confidence: 99%
“…ADDITION-Europe provides a more contemporary comparator for SOUL-D [6]. Early ACTID, an intervention study examining the effects of exercise in new-onset type 2 diabetes in south west England, which also recruited patients with diabetes of short duration, did not report HbA 1c at diagnosis, or prevalence of retinopathy [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both patients and healthcare professionals have reported that the OGTT is a barrier to attending screening [19]. The ADDITION-Europe study used a variety of screening methods to establish a cohort with screen-detected type 2 diabetes [20]. Centres that used a three-step approach, combining a risk score followed by a random blood glucose test followed by an OGTT, had a significantly greater uptake compared with a one-step approach using the OGTT only [15].…”
Section: Discussionmentioning
confidence: 99%
“…Participants diagnosed with type 2 diabetes were subsequently managed according to the treatment regimen to which their practice had been allocated: routine care or intensive treatment [18]. For individuals found to have impaired fasting glucose (IFG) or impaired glucose tolerance (IGT) [17], and/ or a high CVD risk (SCORE >5 points), practitioners were encouraged to manage cardiovascular risk factors according to national guidelines [19], including annual cardiovascular risk assessment and diabetes tests.…”
Section: Introductionmentioning
confidence: 99%